Ethos: o discurso político em cena - Soares, André Santos (2019)
The theme of this study is the constitution of the scenography and the discursive ethos in political speeches given by João Doria, in the period in which he was candidate and mayor of São Paulo and it is based on the Discourse Analysis of French Line (AD), which has been shown to be applicable to researches of different discourses and to privilege the subject. With the enunciative-discursive perspectives proposed by Maingueneau in Discourse Analysis, our general objective is to analyze speeches of the mayor João Doria, given at the time when he was mayor of the city of São Paulo, in the years 2017 and 2018. The reason that motivates us to do this research is the possibility to examine the political discourse and strategies of your organization. The way Brazilian politicians act today disappoints us and, therefore, political discourses need reflections that allow the public machine, controlled by politicians, to turn to the people and make the politician stop thinking about yourself. Our specific objectives are to identify the construction of set design and the constitution of the discursive ethos in speeches given by João Doria; to verify linguistic-discursive strategies and to understand the effects of meaning created by interdiscourse and to relate them to social and discursive memory. The results of the analysis allow us to conclude that the constructed discursive ethos is controversial, since the enunciator plays with characteristics of father, husband, religious, man of the people, with the desire to join his discourse with his co-enunciator. The discursive ethos constructed in set design is a strategy of adherence inherent in discourse